The Hard Problem and the Tyranny of the Loser - Stan Cheung; Marco Mariotti; Roberto Veneziani (Queen Mary University of London, School of Economics and Finance, 2024)
A Hard Problem is a collective choice problem in which the only feasible alternatives apart from the status quo consist of a welfare gain to some people (the Winners) and a welfare loss to the others (the Losers). These problems are typical in a number of settings, such as climate action, anti-trust regulation, and tax design. We study how to make collective choices when faced with Hard Problems. We find that requiring a relatively weak fairness condition, which we call Expansion Solidarity, necessarily leads to a dictatorship of the Losers, no matter how small their number. Even one single Loser must be given the power to veto any departure from the status quo, regardless of the number of Winners, how large the gains, or how small the loss.
Keywords: D63; D70; 330; Pareto improvements; hard choices; solidarity; compromises; maximin difference